2017
DOI: 10.1242/dmm.030114
|View full text |Cite|
|
Sign up to set email alerts
|

Lysyl oxidases regulate fibrillar collagen remodelling in idiopathic pulmonary fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive scarring disease of the lung with few effective therapeutic options. Structural remodelling of the extracellular matrix [i.e. collagen cross-linking mediated by the lysyl oxidase (LO) family of enzymes (LOX, LOXL1-4)] might contribute to disease pathogenesis and represent a therapeutic target. This study aimed to further our understanding of the mechanisms by which LO inhibitors might improve lung fibrosis. Lung tissues from IPF and non-IPF subjects were exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
110
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 119 publications
(123 citation statements)
references
References 53 publications
7
110
0
Order By: Relevance
“…Thus, our data were consistent with previous reports in which it was observed that LOXL2 transcript levels were increased in IPF 10,22 .…”
Section: Loxl2 Transcript Levels Are Elevated In Both Ipf Lung Biopsisupporting
confidence: 94%
See 2 more Smart Citations
“…Thus, our data were consistent with previous reports in which it was observed that LOXL2 transcript levels were increased in IPF 10,22 .…”
Section: Loxl2 Transcript Levels Are Elevated In Both Ipf Lung Biopsisupporting
confidence: 94%
“…2A) but the expression of LOXL2 was almost exclusively extracellular in explanted lung samples ( Fig 2B). The latter finding was consistent with previous findings that this enzyme is secreted and predominately localizes to the ECM in the IPF lung 22 .…”
Section: Loxl2 Protein Is Present In Both Ipf Lung Biopsies and Lung supporting
confidence: 93%
See 1 more Smart Citation
“…This in vivo experiment suggested that BAPN has a role in tumor stroma or surrounding epithelium as LOX does not have a direct impact on tumor cell viability . BAPN has also been tested in IPF, reducing stiffness and returning collagen remodeling to baseline levels (Table , Entry 3) . Furthermore, LOX, LOXL2, and LOXL3 were identified at higher levels in human donor vessels of those diagnosed with idiopathic pulmonary arterial hypertension .…”
Section: Modulation Of Loxl2 Activitymentioning
confidence: 95%
“…The absence of cells in the dECM hydrogels would mean there were no new covalent cross-links established within the hydrogels. The greater degree of matrix organization in the IPF tissue (26) and the stiffer fibroblasts within these tissues (14) would also contribute to the differences in stress relaxation.…”
Section: L702mentioning
confidence: 99%